2020
DOI: 10.3389/fonc.2020.00295
|View full text |Cite
|
Sign up to set email alerts
|

Germline and Somatic BRCA1/2 Mutations in 172 Chinese Women With Epithelial Ovarian Cancer

Abstract: Objective: Despite several nationwide cohort studies of germline BRCA1/2 mutations and several small cohort studies of somatic BRCA1/2 mutations in Chinese epithelial ovarian cancer (EOC) patients, little is known about the impact of these findings on survival outcomes in this population. In this study of 172 retrospectively recruited Chinese EOC patients, germline and somatic BRCA1/2 mutations and their value for predicting survival outcomes were evaluated. Methods: Unselected patients who visited the study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 63 publications
4
18
3
Order By: Relevance
“…Interestingly, in both the overall population and stage III and IV patients, sBRCA did not show any advantage in terms of PFS, PFS2, and OS as compared to wild-type patients. Overall, our results confirm the recent results of You and colleagues [ 27 ] and are apparently in contrast with previous works by Lesnock et al [ 24 ] and Hennessy et al [ 3 ]. Furthermore, no significant differences in PFS, PFS2, and OS were observed between SNVs/indels and CNVs, suggesting that these populations are homogeneous in terms of outcome, while they seem to differ from gBRCA patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Interestingly, in both the overall population and stage III and IV patients, sBRCA did not show any advantage in terms of PFS, PFS2, and OS as compared to wild-type patients. Overall, our results confirm the recent results of You and colleagues [ 27 ] and are apparently in contrast with previous works by Lesnock et al [ 24 ] and Hennessy et al [ 3 ]. Furthermore, no significant differences in PFS, PFS2, and OS were observed between SNVs/indels and CNVs, suggesting that these populations are homogeneous in terms of outcome, while they seem to differ from gBRCA patients.…”
Section: Discussionsupporting
confidence: 87%
“…A few small cohort studies have previously shown that, like gBRCA, pathogenic sBRCA variants have a similar positive impact on OS as well as platinum and PARP inhibitor sensitivity [ 3 , 24 , 25 , 26 ]. On the other hand, a more recent study found no significant impact of sBRCA mutations on progression-free survival (PFS) or OS [ 27 ]. Nevertheless, all these studies suffered from relevant shortcomings, particularly in terms of the copy number variation (CNV) analysis of BRCA genes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, You et al identified five recurrent variants in 172 Chinese women with epithelial ovarian cancer, including three pathogenic mutations (BRCA1 c.5470_5477delATTG GGCA and c.66dup and BRCA2 c.1963delC) and two VUS missense mutations (BRCA2 c.1568A>G and c.6325G>A) [29]. However, these potentially pathogenic mutations above were not validated in our current study.…”
Section: Discussioncontrasting
confidence: 67%
“…To date, several studies have reported the BRCA1/2 pathogenic variants from breast or ovarian cancer in Chinese populations with diverse results. A meta-analysis collected 94 publications with 2128 BRCA1/2 variant records which showed several high-frequency variants but no potential founder variants were identified [26], for example, the two highest recurrent variants c.5470_5477delATTGGGCA [27][28][29] in BRCA1 and c.3109C>T in BRCA2 [25,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation